Host-Symbiont Specificity Expressed during Early Adsorption of Rhizobium meliloti to the Root Surface of Alfalfa - Caetano Anollés, Gustavo (1986)
Early (4 h) adsorption of Rhizobium melioti L5-30 in low numbers to alfalfa roots in mineral solution was examined for competition with other bacterial strains. All tested competitor strains decreased the adsorption of L5-30 by extents which depended on the strain and its concentration. The decrease of adsorption by R. meliloti competitors (all of them infective in alfalfa) was nearly complete at saturation (97 to 99% decrease). AU other heterologous rhizobia and Agrobacterium tumefaciens at saturating concentrations (106 to 107 per ml) decreased adsorption of L5-30 only partially, less than 60%. The differential effects of homologous and heterologous competitors indicate that initial adsorption of R. meliloti to the root surface of its host occurs in symbiont-specific as well as nonspecific modes and suggest the existence of binding sites on roots which are highly selective for the specific microsymbiont in the presence of other heterologous bacteria even in very unfavorable (less than 10-4) symbiont-competitor concentration ratios.